KANDUNGAN NIKOTIN DALAM ASAP ROKOK PASIF CIGARET NON FILTER TERKENAL DI INDONESIA - Ikhwan Resmala Sudji; Mustanir - (Universitas Andalas, 2008)
ABSTRACT Passive smoking has higher health risk than active smoking like coronary heart diseases, lung cancer and mortality level. Nicotine is main contain in cigarettes smokes that caused addictive. The nicotine level of the side stream smoke from Indonesia non-filter cigarettes brand X was analyzed by Gas chromatography-Mass spectrophotometer and Cundiff-Markunas methods for the level of nicotine employing modified smoking standard, namely two puff/min and then were trapping in HCl 0.1 N. The total alkaloid result from 13.745 g burned tobacco (10 cigarettes) was 0.130 g. The nicotine as total alkaloids levels with Cundiff-Markunas methods was 66.860% and the nicotine level with gas chromatography-mass spectrophotometer was 10.05%. Keywords: nicotine, cigarettes smokes, passive cigarettes smokes.